Making modern music. (16th December 2019) - Bennett, Andy
Abstract : Released in September 1982, the album Signals by Canadian band Rush marked a dramatic musical shift for the band away from the hard rock and progressive rock styles that had earned them success during the 1970s to the pop styles of the early 1980s. Signals took fans and music critics by surprise at the time of its release and was also responsible in part for Rush's decision to part company with long-term producer Terry Brown given his apparent ambivalence about the new musical direction suggested by the album. This article offers a critical reappraisal of Signals and its place in Rush's musical legacy. Thus, it is argued, in an era when the heavy and progressive rock styles on which Rush had based much of their musical output up to that point became temporarily unfashionable, Signals provided Rush with a renewed level of artistic currency as a band able to re-invent itself in a way that was relatively unique among heavy and progressive rock artists at the time.